Performance Management System Design of Inspection Bodies in Indonesia - Saefulah Saefulah (Universitas Mercu Buana, 2021)
In order to increase economic growth through infrastructure development in Indonesia, the Government has agreed to increase strategic projects that are urgent to be implemented in the short term. The total project investment reaches IDR 4.183 trillion must be controlled and managed properly, this is where the Inspection Body is needed. The number of Inspection Bodies in Indonesia registered with the National Accreditation Committee (KAN) is 169 institutions. Of the total inspection bodies, 120 are active and have ISO 17020 certificates, while 44 other inspection bodies have their operational licenses revoked and 5 other inspection bodies have been suspended. Seeing this phenomenon, the question arises, why do 26% of the total inspection bodies in Indonesia have their operational permits revoked and the other 3% are frozen? Whereas the existence of this Inspection Agency is very strategic and needed in assisting the supervision of the implementation of national development projects, especially with the large potential benefits, namely 1% of the total value of national projects? This research uses the Balanced Scorecard with Analytical Hierarchy Process (AHP) weighting, the results of performance measurement at inspection service companies in 2020, the high score is financial performance 84%, second place is customer performance at 68%, learning, and growth with a score of 42% is in third place, and the last position is 38% of internal business processes. The total score of the inspection service company's performance is 231% (with an average of 57.76%) which means that the performance of the inspection body/company is currently not good. To test employee satisfaction, a questionnaire was conducted on 23 respondents from 4 inspection companies who were randomly selected from various positions ranging from managers to field inspectors, the results were still quite good, namely 3.99 (scale 1-5).